Hybrid equalization techniques for heterogeneous systems in the millimeter wave band - Correia, Luís Miguel Ribeiro (2021)
With the constant demand for better service and higher transmission rates current technologies are reaching the limits of the channel capacity. Although, technologies such as MIMO and Heterogeneous systems appear to increase the channel capacity by introducing more antennas at the transceivers making the link between users and base station more reliable. Furthermore, the current spectrum, sub-6GHz, is becoming saturated and due to the properties of such frequencies the deployment of heterogeneous systems can introduce some levels of interference. Towards improving future communication systems a new part of the frequencies spectrum available should be used, researchers have their eyes on the mmWave band. This band allows to increase the carrier frequency and respective signal bandwidth and therefore increase the transmission speeds, moreover the properties of such frequencies unlock some advantages over the frequencies used in the sub-6G band. Additionally, mmWave band can be combined with massive MIMO technology to enhance the system capacity and to deploy more antenna elements in the transceivers. One more key technology that improves the energy efficiency in systems with hundreds of antenna elements is the possibility to combine analog and digital precoding techniques denoted as hybrid architectures. The main advantages of such techniques is that contrary to the full digital precoding processing used in current systems this new architecture allows to reduce the number of RF chains per antenna leading to improved energy efficiency. Furthermore to handle heterogeneous systems that have small-cells within the macro-cell, techniques such as Interference Alignment (IA) can be used to efficiently remove the existing multi-tier interference. In this dissertation a massive MIMO mmWave heterogeneous system is implemented and evaluated. It is designed analog-digital equalizers to efficiently remove both the intra an inter-tier interference. At digital level, an interference alignment technique is used to remove the interference and increase the spectral efficiency. The results showed that the proposed solutions are efficient to remove the macro and small cells interference.